Macroporous Polyester—Covered Stent in an Experimental Abdominal Aortic Aneurysm Model - El-Khoury, Joe (2001)
Purpose: To validate a recently described animal model of abdominal aortic aneurysm (AAA) and to assess a new macroporous polyester—covered stent for endovascular AAA exclusion. Methods: Twenty adult sheep had AAAs surgically created by replacing a segment of the infrarenal aorta with an autologous jugular venous graft. Three months later, surviving animals underwent percutaneous implantation of macroporous polyester—covered nitinol stents; 3 animals with untreated AAAs served as controls. Follow-up surveillance included spiral computed tomography at 1 month and digital subtraction angiography at 3 and 6 months. Endografted animals were sacrificed at 1, 3, and 6 months after implantation; specimens from all animals were examined grossly and microscopically. Results: Seven (35%) animals died within 24 hours of causes related to the technique; 1 animal developed paraplegia and was sacrificed on day 1. Three (25%) animals died of spontaneous aneurysm rupture at <10 days, and 6 received the stent-graft at 3 months. The macroporous cover did not prevent continued perfusion of the sac early after stent-graft deployment, but all aneurysms were excluded on the 1-month CT. Conclusions: Spontaneous AAA rupture occurred earlier and was not as frequent as previously described for this model. Implantation of the covered stent was feasible, but aneurysm exclusion was not immediate.